Individual Differences in Parental Support for Numeracy and Literacy in Early Childhood - Leanne Elliott; Peter Zheng; Melissa Libertus (MDPI AG, 2021)
Past research has examined parental support for children's math and reading skills in the early years through parents' reports of their activities with their children in somewhat inconsistent ways. In this study, we use data from a large sample of parents (n = 259; 103 males) collected through Amazon's Mechanical Turk to examine dimensions of parental enrichment in both support for literacy and numeracy skills at home. Additionally, we examine how socioeconomic resources as well as parental beliefs relate to these dimensions of the home literacy and home numeracy environment. Factor analyses revealed two dimensions of literacy activities (i.e., passive and active literacy activities) and three dimensions of numeracy activities (i.e., numeracy applications, basic numeracy, and written numeracy activities). Income was positively associated with active literacy activities, whereas parents' educational attainment was negatively associated with active literacy activities and written numeracy activities. Additionally, parental beliefs, including their beliefs about the importance of literacy and math skills as well as their perceived responsibility for teaching their children reading, math, and language skills, related to home literacy and numeracy activities in distinctive ways. These results suggest that future research should explore parental enrichment practices with greater nuance, particularly when examining associations with socioeconomic status.